Dietary Pattern and Psychological Stress Are Not Associated with Gastro-oesophageal Reflux Symptoms in Female Preclinical Medical Students: A Precision-Focused Cross-Sectional Study - Najwa Faradila Yuvitri; Sri Wahyuningsih; Wilfadri Putra Jonesti; Aulia Chairani (HM Publisher, 2026)
Background: Gastro-oesophageal reflux disease is among the most prevalent chronic gastrointestinal disorders worldwide and its absolute burden continues to rise, yet studies of behavioural determinants in young adults report statistical significance without magnitude and almost never state the effect size their design could detect. Objective: To estimate the association of dietary pattern and psychological stress with symptom-defined gastro-oesophageal reflux, and the precision with which those associations could be detected, in a restriction-based sample of female preclinical medical students. Methods: This STROBE-compliant cross-sectional study used a restriction-based design to isolate behavioural exposures from adiposity and the other dominant reflux risk factors. Of 120 randomly selected female preclinical medical students at the Faculty of Medicine, Universitas Pembangunan Nasional